Self-assembled peptide and protein nanostructures for anti-cancer therapy: Targeted delivery, stimuli-responsive devices and immunotherapy - Delfi, Masoud; Sartorius, Rossella; Ashrafizadeh, Milad; Sharifi, Esmaeel; Zhang, Yapei; De Berardinis, Piergiuseppe; Zarrabi, Ali; Varma, Rajender S; Tay, Franklin R; Smith, Bryan Ronain; Makvandi, Pooyan (Nano today, 2021)
Self-assembled peptides and proteins possess tremendous potential as targeted drug delivery systems and key applications of these well-defined nanostructures reside in anti-cancer therapy. Peptides and proteins can self-assemble into nanostructures of diverse sizes and shapes in response to changing environmental conditions such as pH, temperature, ionic strength, as well as host and guest molecular interactions; their countless benefits include good biocompatibility and high loading capacity for hydrophobic and hydrophilic drugs. These self-assembled nanomaterials can be adorned with functional moieties to specifically target tumor cells. Stimuli-responsive features can also be incorporated with respect to the tumor microenvironment. This review sheds light on the growing interest in self-assembled peptides and proteins and their burgeoning applications in cancer treatment and immunotherapy.
Keywords: Drug delivery; Immunotherapy; Virus-like particles; Stimuli-responsive; Self-assembled peptides and proteins; Cancer therapy